The effect of hypophysectomy and subsequent replacement therapy with sheep prolactin or bovine growth hormone on the lactose synthetase activity of rabbit mammary gland - Jones, E. A. (1972)
1. The effects of hypophysectomy and replacement therapy with sheep prolactin and bovine growth hormone on the lactose synthetase activity of the mammary glands of lactating rabbits were studied. 2. There was an approximately fourfold decline in the lactose synthetase activity of homogenates calculated on a DNA basis within 6–7 days of hypophysectomy. Prolactin reversed this decline but growth hormone had no effect. 3. Changes in the properties of a particulate fraction isolated from the glands indicated that a decline in the effective concentration of α-lactalbumin was one factor contributing to the decreased lactose synthetase activity after hypophysectomy. 4. As the changes in lactose output produced by hypophysectomy and prolactin therapy are much greater than the changes in total lactose synthetase activity it is concluded that the activity of this enzyme is not the main factor controlling lactose output under these conditions.